Cabaran Tarbiah dalam Era Dakwah - Yusoff, Yaacob (Jurnal Usuluddin, 1996)
This article is to explore the agenda of da'wah which has become a central attraction in today society. Privates sectors are been in making this agenda a formal academic form with the emergence of many institutions and colleges. At the same time, the movement of da'wah needs the essence of tarbiah, not only through rhetorical approach. What are the problems which hinder us to achieve Islamic tarbiah and what is its relationship to the roles of da'wah which Allah has obligated on us' Therefore this article examines the taxonomy of tarbiah from Islamic perspective. It also examines the hindrames towards Islamic tarbiah which certainly need patience from everybody who are involved. If this question is able to capture the attention of all concerned parties perhaps it will gave way to enhance the roles of tarbiah as an essence of da'wah. But, what is the attitude of the societies where tarbiah has become an agenda in their da'wah' Therefore this article proposes a complementary concept which is arranged in hierarchy according to their capability and function.